Спектр поглинання сумiшi CO та HF для змiнної у часi густини CO - Sizhuk, A. S. (Publishing house "Academperiodika", 2019)
The gas phase spectra of a mixture of hydrogen fluoride (HF) and carbon oxide (CO) are obtained for the interval from 3838 to 3854 cm−1. Using the Fourier transform infrared (FTIR) broadband spectroscopy technique, the arising P-heads of the fundamental and hot bands of OC–HF complex are observed with increasing the pressure of the CO component, while the HF compound has a fixed amount of molecules. The dependence of the integral change in the transmitted intensity on the pressure of carbon monoxide is analyzed in vicinities of the P-heads of the fundamental band at 3939.12 cm−1 and the hot band at 3944.5 cm−1.